IMPLEMENTATION OF STEM APPROACH IN THE SECONDARY EDUCATION SYSTEM OF KAZAKHSTAN - Dinara Kazimova; Alma Kostangeldinova; Azhar Kozhabayeva; Saltanat Sadykova (Research Retrieval and Academic Letters, 2024)
The concept of STEM education is based on the idea of improving and renewing the educational system through STEM technologies. STEM (or STEAM) education acts as a bridge connecting the educational process with career development and professional growth, preparing students for a technologically advanced world. The implementation of STEM and STEAM approaches requires a transformation of the secondary education system’s content, fundamentally new approaches to the organization of practical classes, equipping school laboratories and workshops with modern equipment, and carrying out a systematic process of developing STEM competencies in students. In STEM education, students gain more autonomy, becoming active participants in the learning process compared to the traditional lesson format [1].